2000
DOI: 10.1055/s-2007-978581
|View full text |Cite
|
Sign up to set email alerts
|

Desaturation Function Does Not Decline after Menopause in Human Females

Abstract: Aging appears to decrease delta6-desaturase activity in males, but in females it is uncertain. delta6- and delta5-desaturase functions were investigated in pre- and post-menopausal women who were normoglycemic or had type 2 diabetes (2 x 2 factorial, n = 37). Subjects were compared for indicators of diabetic control, estrogen levels, fatty acid profiles and indices of delta6- and delta5-desaturase activity. Diet intakes that were compared to determine whether results were a function of dietary factors known to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 11 publications
(17 reference statements)
0
8
0
Order By: Relevance
“…Aging may decrease D6D activity in rodents and humans. Decreased activity of D6D with age may not apply to different cohorts, as either males or mixed gender samples have usually been analyzed [ 69 ]. Studies of aging women were unable to document a similar decline in enzyme activity, primarily because of the released suppression of desaturase activity with the loss of estrogen after menopause.…”
Section: Discussionmentioning
confidence: 99%
“…Aging may decrease D6D activity in rodents and humans. Decreased activity of D6D with age may not apply to different cohorts, as either males or mixed gender samples have usually been analyzed [ 69 ]. Studies of aging women were unable to document a similar decline in enzyme activity, primarily because of the released suppression of desaturase activity with the loss of estrogen after menopause.…”
Section: Discussionmentioning
confidence: 99%
“…Ratios of blood fatty acids have been used previously as markers for desaturation enzyme (the rate-limiting steps in essential fatty acid metabolism) potentials in humans. [24][25][26][27] The desaturase potential ratios were calculated as follows; ⌬6 desaturase potential = (18:3n-6 + 20:3n-6) / 18:2n-6, ⌬5 desaturase potential = (20:4n-6 + 22:4n-6) / 20:3n-6, total desaturase potential = (18:3n-6 + 20:3n-6 + 20:4n-6 + 22:4n-6 + 22:5n-6) / 18:2n-6.…”
Section: Methodsmentioning
confidence: 99%
“…The lack of difference between the ⌬6 and ⌬5 desaturase potentials of the premenopausal and postmenopausal women not receiving HRT shown in study A has been demonstrated previously. 27 Increased synthesis and levels of AA with oral estrogen use, and the observation of increased thrombotic events with oral HRT intervention in the Heart and Estrogen/Progestin Replacement Study 11 and the Women's Health Initiative Trial, 16 may possibly be related as AA is a precursor of the eicosanoid thromboxane A 2 , a potent platelet aggregator. In addition, myocardial infarction and stroke were associated with higher levels of 20:3n-6 in serum phospholipid in the Edinburgh Artery Study.…”
Section: Stark Et Almentioning
confidence: 99%
“…In humans, obesity decreases the metabolism of essential fatty acids due to reduced activities of desaturases [15]. Studies on animals and humans demonstrated that the gender-related difference in D 5 and D 6 desaturase activity is possibly mediated by sex hormones [16][17][18]. Normally, D 5 and D 6 desaturases and elongases exhibit affinity to metabolize n-3 more than n-6 PUFAs provided that both exist in the physiological ratio of 1: 1-4 [4,10].…”
Section: What Are Essential and Polyunsaturated Fatty Acids?mentioning
confidence: 99%